2016
DOI: 10.7748/ncyp.28.2.16.s21
|View full text |Cite
|
Sign up to set email alerts
|

Toilet training for children with autism

Abstract: Toilet training is one of the key developmental milestones of early childhood and there is growing evidence that it is now being initiated later than it was 50 years ago. This article explores the reasons why this is happening and considers the effect on children with autism and related conditions. It also examines the literature to discover the approaches to toilet training for this group. Research into this area has generally focused on small numbers of children and incorporated modified versions of Azrin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Therefore, incontinence is a significant barrier to good quality of life for people with autism. Lower cognition and verbal levels correlate significantly with the age at which bowel and urine training is completed in children with autism[ 30 ]. Approximately 30% of children with autism have anxiety related to toileting, with verbally impaired individuals having the most.…”
Section: Neurological Disordersmentioning
confidence: 99%
“…Therefore, incontinence is a significant barrier to good quality of life for people with autism. Lower cognition and verbal levels correlate significantly with the age at which bowel and urine training is completed in children with autism[ 30 ]. Approximately 30% of children with autism have anxiety related to toileting, with verbally impaired individuals having the most.…”
Section: Neurological Disordersmentioning
confidence: 99%
“…The neurodevelopmental sub-cohort was older at the time of BMP compared to the FC only group. Previous studies have shown children with neurodevelopmental disorders, like ASD, have significant barriers to potty training (23). It is possible this initial delay is realized as an age gap at the time of BMP enrollment between patients with a neurodevelopmental disorder and those without.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there are therapy costs, additional childcare costs, medical costs and other considerations. For example, because of developmental delays, toilet training takes much longer (Richardson 2015 ). Progress through the school system may also have to be extended: one cannot blithely assume that the special needs child will advance along with his or her age cohort despite this being a policy imperative (Department of Education 1996 ).…”
Section: Discussionmentioning
confidence: 99%